2021
DOI: 10.3390/su14010222
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Sustainability and Carbon Neutrality in Higher Education Institutions: A Review

Abstract: Universities and higher education institutions play an important role in achieving a sustainable future through their teaching and by undertaking cutting edge research to combat climate change. There have been several efforts towards a sustainable future and achieving carbon neutrality at higher education institutions in Australia and around the world. This study has reviewed the sustainability strategies of numerous universities in Australia and has identified as study cases six universities that are committe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…In addition to this, in their study, Cheng et al pointed out that some Nordic countries have developed and implemented Pigouvian tax mechanisms to help achieve carbon neutrality through tax policies (Cheng et al 2021 ). A study by Sen et al from Victoria University, Australia, suggested that the creation, expansion, and dissemination of knowledge and learning about carbon neutrality would help to achieve the country’s goal of achieving carbon neutrality eventually and that this initiative and policy is clearly reflected in university educational institutions (Sen et al 2022 ). The development of initiatives, policies, and measures related to reducing greenhouse gas emissions in each country is essential to fully achieve the goal of carbon neutrality by 2050 or 2060.…”
Section: Worldwide Initiatives To Achieve Carbon Neutralitymentioning
confidence: 99%
“…In addition to this, in their study, Cheng et al pointed out that some Nordic countries have developed and implemented Pigouvian tax mechanisms to help achieve carbon neutrality through tax policies (Cheng et al 2021 ). A study by Sen et al from Victoria University, Australia, suggested that the creation, expansion, and dissemination of knowledge and learning about carbon neutrality would help to achieve the country’s goal of achieving carbon neutrality eventually and that this initiative and policy is clearly reflected in university educational institutions (Sen et al 2022 ). The development of initiatives, policies, and measures related to reducing greenhouse gas emissions in each country is essential to fully achieve the goal of carbon neutrality by 2050 or 2060.…”
Section: Worldwide Initiatives To Achieve Carbon Neutralitymentioning
confidence: 99%
“…PAS 2060 specifies requirements to be met by entities seeking to demonstrate carbon neutrality. Although PAS 2060 was published in 2014 before the Paris Agreement was established, it was selected to be included in the guidelines to be reviewed due to being internationally recognized and widely adapted in setting climate goals and working to achieve them (Birkenberg and Birner 2018;Zhou 2020;Gaurangi et al 2022;Rayer et al 2022). The specification provides standard definitions and a method to validate entities' actions toward becoming carbon neutral.…”
Section: Pas 2060mentioning
confidence: 99%
“…Studies such as Leal Filho et al ( 2018) suggest that the increase in digital technologies' use in HE classrooms as a major part of SD initiatives in the HE sector. Some of the common initiatives implemented by HEIs can be classified into eight "sustainability categories", namely built environment, energy, food, and gardens, greenhouse gas emissions, natural environment, resource and waste management, transport, and water (Sen et al, 2021). In addition, there is a growing body of literature on the topic of "education for sustainability."…”
Section: Mezzo-level He Administration Levelmentioning
confidence: 99%